Issues that impact on effective family literacy provision in England - Swain, Jon; Brooks, Greg (International Journal about Parents in Education, 2023)
This paper raises and discusses a series of key issues that arose during a 20-month evaluation project concerning the impact of family literacy programmes on the skills of parents and their children. Using a range of mixed methods, the research was based on 74 family literacy programmes in England and involved 583 parents and their children. The majority of previous evaluations of family learning have been quantitative and concentrated on children’s literacy outcomes; they have tended to ignore issues from qualitative research (which can both enable and constrain effective provision), many of which are of great interest to policy-makers. The specific issues raised in this paper coalesce around themes of recruitment; accreditation; the educational profile of parents (including the scarcity of men); the physical teaching and learning environment; the competing agendas between local authorities and schools; and planning opportunities between adult family literacy tutors and early years teachers.